2010
DOI: 10.2174/138161210794455049
|View full text |Cite
|
Sign up to set email alerts
|

The Estrogenic Burden on Vascular Risk in Male-to-Female Transsexuals

Abstract: Transsexualism refers to individuals that identify themselves as members of the opposite gender and who strive to acquire the physical appearance and psychosocial role compatible with that gender. Gender reassignment therapy is applied through hormonal treatment ± surgical intervention in addition to psychological support. Hormone treatment for male-to-female transsexuals includes estrogen supplementation ± suppression of androgen secretion or action. Sex hormones are important determinants of the metabolic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
(149 reference statements)
0
9
0
Order By: Relevance
“…Two studies in transsexual populations indicate that MtoF treated with ethinyl estradiol, compared with other types of estrogen, are more prone to venous thrombosis (44) and to cardiovascular mortality (14). The effects of various types of estrogens and their route of administration in transsexual persons have been excellently reviewed (53).…”
Section: Route Of Administration Of Estrogensmentioning
confidence: 99%
“…Two studies in transsexual populations indicate that MtoF treated with ethinyl estradiol, compared with other types of estrogen, are more prone to venous thrombosis (44) and to cardiovascular mortality (14). The effects of various types of estrogens and their route of administration in transsexual persons have been excellently reviewed (53).…”
Section: Route Of Administration Of Estrogensmentioning
confidence: 99%
“…The increases in Hcy levels with natural menopause and the decrease with menopausal hormone replacement therapy (Bednarek-Tupikowska et al, 2005) suggest a close relationship between Hcy metabolism and estrogen levels (Mijatovic & van der Mooren, 2001). A study of male-to-female transsexuals reported the relationship between reduced circulating Hcy and sex reassignment therapy (Lioudaki, Ganotakis, Mikhailidis, & Nair, 2010), intuitively demonstrating that the sex differences in the Hcy were associated with estrogen protection. This protection from HHcy in women with BD may be related to the estrogen effects on Hcy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify and optimize control of these medical co-morbidities prior to initiating the hormonal phase of treatment, as they can be exacerbated by hormones such as estrogen (1719). Close attention should be paid to the possibility of cardiovascular events, as accruing evidence has suggested that MTF GD patients may be at an increased cardiovascular risk (2022). Twenty-six percent of patients were smokers at initial presentation which is in line with the national average of 29% (23).…”
Section: Discussionmentioning
confidence: 99%